Molecular characterization of Malaysian swiftlet species and development of PCR-ELISA method for rapid identification of edible bird's nest - Sue, Mei Jean (2016)
Edible birds’ nest (EBN) is a precious functional food that has been used for several hundred years by Chinese communities around the world. EBN is mainly comprised of a type of secretion from the salivary gland of 4 swiftlet species in the Aerodramus genus. In Malaysia, EBNs are obtained from 2 Aerodramus species; Aerodramus fuciphagus and Aerodramus maximus. Due to the limited supply and high price of genuine EBN, counterfeit EBN products are often found in the market. To differentiate the genuine nests from adulterants, one of the suggested methods is to look at the molecular level of EBN swiftlet species to identify unique sequence in each species. Therefore, the general objective of this study was to conduct a molecular characterization of Malaysian swiftlet species and develop a PCR-ELISA method for rapid identification of EBN. The specific objectives were (i) to characterize Malaysian swiftlet species based on sequencing and phylogenetic analysis of cyt-b and ND2 genes, (ii) to design and optimize primers, probes and PCR-ELISA protocols for the detection of EBN, and (iii) to evaluate the performance of the developed PCR-ELISA using commercially purchased EBN and adulterants. For phylogenetic analysis of Malaysian EBN swiftlet species, DNA extracted from EBN and swiftlet pectoral samples were sequenced at the cyt-b and ND2 gene regions to serve as phylogenetic markers. The information obtained were used to confirm the identity for each species by referring the results to the NCBI website, construct the phylogenetic tree of Malaysian swiftlet species and used for probe design for the development of PCR-ELISA method. From the phylogenetic analysis, it was observed that Apus affinis and Aerodramus species have a genetic distance of 11.1-14.7% and 18.6-20.0%, respectively, for cyt-b and ND2 gene. Amongst the Aerodramus species, both A. fuciphagus and A. maximus have a genetic distance of 7.5-9.5% for cyt-b gene and 8.9-11.5% for ND2 gene, indicating that both species were more closely related to one another than A. affinis. Amongst the white nest swiftlets, they were further separated into either natural cave nests or nests from swiftlet ranch, with genetic distance of 1.7-2.1% for cyt-b gene and 2.0-2.5% for ND2 gene respectively. Not only that, the sequenced data also allowed the successful identification of unique gene regions displaying SNPs as potential molecular markers to differentiate between Malaysian EBN swiftlet species. By identifying DNA sequences containing at least 2 unique SNPs between species of A. fuciphagus, A. maximus and A. affinis as potential probe regions, specific probes and primers targeting species-specific regions on cyt-b and ND2 were successful identified. For the development of PCR-ELISA, several factors were also successfully optimized. It was found that optimized results were obtained when 10 × digoxigenin-labelled PCR products were hybridized with 7.5 pmol/well biotin-labelled probe concentration, at 37oC for 1 hr. A. affinis gave lower O.D. readings compared to both Aerodramus species and thus, the cut-off value for detection of EBN authenticity is set at 1.5. The performance of developed PCR-ELISA was evaluated using commercial EBN samples and adulterants. When tested against a commercially purchase fake nest and three common adulterants; the probe does not recognize the adulterants. This shows the specificity of the probe towards the Aerodramus species but not the adulterants, allowing detection of authentic EBN in the sample. Finally, when the performance of PCR-ELISA was evaluated through the spiking test, EBN samples that were spiked with higher concentrations of adulterants have O.D. readings that tend to drop in accordance to the nests concentration. Overall, Malaysian swiftlet species were successfully characterized based on sequencing and phylogenetic analysis of cyt-b and ND2 genes. The primers and probe for PCR-ELISA as well as PCR-ELISA protocols were successfully developed and optimized. The performance of the developed PCR-ELISA was also found to be specific to EBN when the assay was tested using commercially purchased edible birds’ nests and adulterants. In conclusion, this study had successfully achieved all the objectives of the study and with the successful development of PCR-ELISA for detecting genuine EBN from samples that were spiked with adulterants, the EBN industry will be able to increase or regain back the confidence level of the consumers and increase the sales of EBN.